Deteksi Strain Pseudomonas solanacearum Penghasil Bakteriosin - Triwidodo Arwiyanto; Sudarmadi Sudarmadi; I. Hartana (Universitas Gadjah Mada, 1996)
The capability of Pseudornonas solanacearum to produce bacteriocin was investigated with theuse oj Casamino-acid Peptone Glucose Agar. All strains tested produce bacteriocm withvarious spectra. Strain 6, 36 and ./9 inhibited almost all of the other strains. The avirulenttype of those three strains. i.e. 6-op. 36-op and -19-op, still produced bacteriocln on the samemedium. The.concentratlon of carbon source and acidity of the medium did not have any effecton the bacteriocin production. The bacterioctn produced by strains 6-op, 36-op and 49-opwere inactivated at 70°C for 30 minutes.